Significant Changes in Low-Abundance Protein Content Detected by Proteomic Analysis of Urine from Patients with Renal Stones After Extracorporeal Shock Wave Lithotripsy - Elena Carestia; Fabrizio Di Giuseppe; Mohammad Kazemi; Massoumeh Ramahi; Uditanshu Priyadarshi; Patricia Giuliani; Piergustavo De Francesco; Luigi Schips; Carmine Di Ilio; Renata Ciccarelli; Patrizia Di Iorio; Stefania Angelucci (Biology)
Extracorporeal shock wave lithotripsy (ESWL), although a highly effective method for the treatment of kidney stones, can cause significant kidney damage. Since urinary protein composition directly reflects kidney function, proteomic analysis of this fluid may be useful to identify changes in protein levels induced by patient exposure to ESWL as a sign of kidney damage. To this end, we collected urine samples from 80 patients with nephrolithiasis 2 h before and 24 h after exposure to ESWL, which were concentrated and subsequently processed with a commercially available enrichment method to extract low-abundance urinary proteins. These were then separated by 2D electrophoresis and subsequently analyzed by a proteomic approach. A large number of proteins were identified as being related to inflammatory, fibrotic, and antioxidant processes and changes in the levels of some of them were confirmed by Western blot analysis. Therefore, although further experimental confirmation is needed, our results demonstrate that ESWL significantly influences the low urinary protein profile of patients with nephrolithiasis. Notably, among the identified proteins, matrix metalloproteinase 7, alpha1-antitrypsin, and clusterin, as well as dimethyl arginine dimethyl amino hydrolase 2 and ab-hydrolase, may play an important role as putative biomarkers in the monitoring and management of ESWL-induced renal damage.